Business Models of Journalistic Startups in Portugal: an Analysis of Product Innovation, Dissemination and Monetization in Media Enterprises - Crespo, Miguel; Pinto-Martinho, Ana; Foà, Caterina; Paisana, Miguel; Caldeira Pais, Pedro (Nordic Journal of Media Management, 2020)
Purpose: Journalistic startups are thriving around the world, bringing new approaches to the news media environment in terms of concepts, contents, dissemination, internal organization, and business models. This research is relevant to create a prospective view on the evolution of the news media business in the next years, also allowing us to identify some trends and experiences which can be useful to future researchers work, and for professionals of news media companies, startups or not, to get some insights that might help to develop (or even save) their own businesses. Methodology: Through semi-structured interviews with the editorial managers of each of the research subjects, we tried to understand the genesis, concepts, processes, and goals of these startups. We made a thematic analysis of the content, using an adapted version of the IPTC NewsCodes, to understand the editorial approach in terms of Genre, Subject, Media Topic, Media, and Priority in each of the startup’s publication platform. To better understand the business, we did a business model mapping, using the Business Model Canvas conceptual tool, for all the subjects. Findings/Contribution: The main findings indicate that all the startups in this research started through the identification of a problem or a need, within a small group of friends or colleagues. They all try to fit into a niche and not compete with legacy media, and search for alternative financing sources. All the teams are small, produce mainly long form reporting and interviews, and use mostly written text - but video tends to grow in volume. All the subjects work for niche audiences, by location or interests. These results contribute to create a structured and broader view of the journalistic startups scene in Portugal, but can also help other researchers to apply similar methods to map different realities, in geographical or thematical terms. This research can also contribute to better understanding the challenges that digital news media face in this networked society we live in.